Computational Methods and Experimental Measurements XVII 2015
DOI: 10.2495/cmem150381
|View full text |Cite
|
Sign up to set email alerts
|

The design of a small-scale multi-stage desalination plant driven by the exhaust of diesel generators

Abstract: The present study provides an energy-saving design of a desalination plant that uses the waste heat of the exhaust of a diesel generator. The proposed model consists of a multistage flash (MSF) desalination unit in which the sea water is heated by the flue gases instead of steam. A mathematical model is derived to design the entire plant including the waste heat recovery heat exchanger and the MSF plant. The model is flexibly designed in order to deal with wide range of diesel generators rates and any number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…It was concluded that the amount of freshwater produced by a diesel generator could be estimated by the second order polynomial as 0.36 + 2.7 × 10 −3 (kVA) + 3.1 × 10 −6 (kVA) 2 [19]. Table 6 shows the values determined in the other case studies and validates the proposed small scale multigeneration desalination design as a viable option for producing power and fresh water.…”
Section: Validationmentioning
confidence: 60%
See 3 more Smart Citations
“…It was concluded that the amount of freshwater produced by a diesel generator could be estimated by the second order polynomial as 0.36 + 2.7 × 10 −3 (kVA) + 3.1 × 10 −6 (kVA) 2 [19]. Table 6 shows the values determined in the other case studies and validates the proposed small scale multigeneration desalination design as a viable option for producing power and fresh water.…”
Section: Validationmentioning
confidence: 60%
“…In a combined cycle cogeneration design the net power that is produced equals the sum of all the power within the system as denoted in Equation (19). This includes: gas turbine power output (positive), compressor power input (negative), steam turbine power output (positive), and pump power input (negative) [20].…”
Section: Combined Cyclementioning
confidence: 99%
See 2 more Smart Citations
“…This creates a seasonal effect on the quality of water produced from this process. Researchers have concluded that production is higher in summer than in winter due to the higher summer feedwater temperatures [10].…”
Section: Introductionmentioning
confidence: 99%